Calcium Sensing receptor expression is downregulated in gastroenteropancreatic neuroendocrine tumours via epigenetic mechanisms - English, KA; Goldsworthy, M; Willis, B; Kooblall, KG; Birla, S; Selberherr, A; Stevenson, M; Shariq, OA; Oberg, AL; Wang, T; Carmichael, J; Mavrommatis, K; et al. (Wiley, 2024)
Gastroenteropancreatic neuroendocrine tumours (GEP-NETs), which may be hormone secreting (e.g gastrinomas and insulinomas) or non-secreting (also known as non-functioning NETs) are associated with severe morbidity and have a median overall survival of 75-124 months. Studies have highlighted the importance of epigenetic mechanisms in GEP-NETs pathogenesis, with the most frequently mutated genes being the epigenetic regulators, MEN1, DAXX, and ATRX. However, the consequences of these aberrant epigenetic mechanisms are poorly understood. The calcium sensing receptor (CASR), a G protein coupled-receptor (GPCR), is epigenetically silenced in cancers, and therefore we examined its role in GEP-NET subtypes. Using RNA-Scope and quantitative PCR analyses in two independent tumour cohorts from Europe (n=18 patients) and the USA (n=46 patients) we showed that CASR mRNA is almost completely absent in gastrinomas, insulinomas and non-functioning pancreatic NETs. Furthermore, immunohistochemical staining confirmed a significant reduction in CaSR protein expression in all GEP-NET subtypes, compared to normal islets. DNA MethylationEPIC and ATAC-Seq analyses in the pancreatic NET cell line QGP-1 showed that the CaSR promoter was both hypermethylated and in a region of closed chromatin. Furthermore, transfection of wild type CaSR into QGP-1 cells decreased cell viability, in keeping with the CaSR having a role in cellular proliferation. In summary, our study reveals that CaSR expression is decreased in GEP-NETs and that this reduced expression is likely due to DNA methylation and chromatin changes. Moreover, we demonstrate that transfection of the CaSR into a PNET cell line reduces cell viability, thereby indicating that the CaSR acts as a tumour suppressor in this tumour type.